Different Culture or Different Mind? Perception and Acceptance of HPV Vaccine in China and in the U.S. Issue 12 (2nd December 2018) - Liu, Sixiao; Yang, Janet Z.; Chu, Haoran; Sun, Shaojing; Li, Haichun
Abstract : Unlike the United States, where human papillomavirus (HPV) vaccines have been available for decades, China recently approved its first HPV vaccines. Setting up a baseline comparison between these two countries, this study examines the influence of message framing, motivational orientation, cultural worldview, knowledge, and gender on young adults' intentions to get vaccinated. Compared to the U.S. participants, Chinese participants perceived HPV as a more severe risk and were more willing to get the vaccine. However, they were also more skeptical about vaccine safety. Inconsistencies with previous research emerged regarding the moderating effects of motivational orientation and cultural worldview. Findings from this study offer important implications for HPV vaccine promotion in China.